Ionic strength and zeta potential effects on colloid transport and retention processes - Samari-Kermani, Mandana; Jafari, Saeed; Rahnama, Mohammad; Raoof, Amir (Colloid and interface science communications, 2021)
In this study, a fully coupled pore scale model was developed with the aim of exploring the effects of ionic strength and zeta potential on colloids transport under favourable and unfavourable conditions. The Lattice Boltzmann-Smoothed Profile method was used to simulate particle-particle and particle-fluid interactions without a need for assumptions of dilute suspension and clean bed filtration. Simulation using a wide range of parameters have shown creation, and breakup of agglomerates. Results are used to obtain time-averaged behaviour of transport properties, such as pore void fraction, conductivity, and surface coverage. We have found that in comparison with zeta potential, increasing ionic strength had a greater impact on particles behaviour. A raise in ionic strength caused a decrease in pore void fraction and its conductivity and an increase in aggregates connectivity. [Display omitted] •The fully coupled fluid flow and colloid transport model successfully simulated aggregates creation and fragmentation.•The shadow effect is dependent on flow velocity, ionic strength and the rolling ability of deposited particles.•Under unfavourable conditions, rolling of particles on the surface prevented clogging and caused reopening of the pore.•Pore clogging and the subsequent reopening of the pore caused fluctuations in conductivity and void fraction.